KARAKTERISTIK ZONASI BATUAN RESERVOAR BERDASARKAN PETROGRAFI, SERBUK BOR, UJI TEKANAN DAN TEMPERATUR DI LAPANGAN PANAS BUMI SOKORIA, KABUPATEN ENDE, PROVINSI NUSA TENGGARA TIMUR: RESERVOIR CHARACTERISTICS BASED ON PETROGRAPHY, CUTTING, PRESSURE AND TEMPERATURE TEST IN SOKORIA GEOTHERMAL FIELD, ENDE REGENCY, NUSA TENGGARA TIMUR PROVINCE - Purbiyantoro, Aldila Jasmine; Agus Didit Haryanto; Euis Tintin Yuningsih; Haris Siagian (Buletin Sumber Daya Geologi, 2020)
Sokoria Geothermal Field is located at Sokoria Village, Ende Regency, Nusa Tenggara Timur Province. Petrographic analysis and Methylene Blue test (MeB) were carried out to estimate the illite-smectite ratio and occurence of other alteration minerals as indicator for cap rock, transition and reservoir zones. Pressure and temperature test (P&T test) was also performed to determine those zonation. The result concludes the geothermal caprock zone is distributed from the surface to the dept of 700 mVD (meter vertical depth), indicated by medium to high MeB index (20 – 80%), as smectite characteristic temperature up to 100°C. The transition zone is located from the depth of 700 mVD to 1100 mVD, with low MeB index (6 – 20%), as illite and illite–smectite characteristic and well temperature up to 200°C. Reservoir zone is located at 1100 mVD, indicated by very low MeB index (<10%),as characteristic of illite, with first appearance of epidote in well W-1 at 1119 mMD (meter measured depth) and well W–2 at 1338 mMD. P&T test shows reservoir temperature reached 250°C.